SISTEM EKONOMI ISLAM DI TENGAH PERTARUNGAN SISTEM EKONOMI KONVENSIONAL - Nasution, Syafri GUnawan (FORUM PAEDAGOGIK, 2014)
AbstractEconomic system are diverse from growth process, ownership, profit share, motivation and attraction. Market economic system (capitalism) and command economic system (socialism) are powerful. Both influence the growth of world economy for orientation and value. Furthermore, they say that none spiritual life is better than spiritual one.In conclusion, Islamic economic system says that there should be moral balance, harmony and equality in life and life after. None and spiritual life development should go conceptually and affectively.